2019
DOI: 10.29252/jech.6.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motivational Interviewing on Hypertension, self-care and Quality of Life of Rural Aged People: Application of Health Belief Model

Abstract: Integrating motivational interviewing and brief behavioral activation ... [20] Effect of educational intervention based on the Health Belief Model ... [21] Development of the Chinese family support scale in a sample of ... [22] Determinants of patient's adherence to hypertension medications ... [23] The association between selfefficacy and hypertension self-care ... [24] Medication adherence measures ... [25] Healthrelated quality of life evaluation of elderly aged 65 years and ... [26] Resolving patient ambiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…At the last of intervention, the mean of SBP and DBP and also the average scores of social support, self-e cacy, and quality of life improved signi cantly. However, were conducted in semi-experimental design and without control group [59].…”
Section: Discussionmentioning
confidence: 99%
“…At the last of intervention, the mean of SBP and DBP and also the average scores of social support, self-e cacy, and quality of life improved signi cantly. However, were conducted in semi-experimental design and without control group [59].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of the study was determined based on a previous study, 11 with a confidence level of 95% and a power of 80%. The observed drop rate was 1.2 percent.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…According to guidelines, patients having systolic blood pressure higher than 140 mm Hg and/or diastolic blood pressure higher than 90 mm Hg based on the average of two or more readings is considered as hypertension. 11 The exclusion criteria encompass three factors: nonattendance at two training sessions, illness resulting in the participant's inability to continue the study, and the participant's lack of willingness to attend and sustain involvement in the research.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically significant improvements were observed in systolic and diastolic blood pressure at the end of this study 39 . In a study conducted by Mohamadian et al (2019) with 120 hypertensive participants over the age of 60, a decreased in the blood pressures of the patients and an increase in their selfefficacy levels were observed 40 , In the study conducted by Mirkarimi et al (2015) with 14 hypertensive individuals, on the other hand, the systolic blood pressures and diastolic blood pressures of the motivational group significantly decreased after 6 months, and it was concluded that motivational interviewing could be used as an effective method in medication adherence and to control the recovery and progress of blood pressure in patients with hypertension 41 .…”
Section: The Effect Of Motivational Interviewing On Hypertensive Individuals' Blood Pressurementioning
confidence: 99%